SHEAR STRENGTHENING OF R/C BEAMS USING AFRP STIRRUPS WITH ANCHORED ENDS (Malaysian Journal of Civil Engineering, 2018)
Many studies have been conducted on the behaviour of reinforced concrete (R/C) beams shear-strengthened with fiber reinforced polymer (FRP) sheets. The studies show that FRP materials can produce good performance when used to carry some portions of shear force in the shear-strengthened beam. However, the performance of the FRP sheets used for shear strengthening is found limited by bond capacity between the FRP sheets and concrete surface. To improve the bond performance, an anchorage system can be introduced to the FRP strengthening scheme. This paper presents experimental and analytical studies conducted to evaluate the contribution and behaviour of aramid fiber reinforced polymer (AFRP) sheets with anchored ends in carrying the shear force in reinforced concrete beams. In the study, nine reinforced concrete beam specimens were fabricated and tested. Test parameters of the study include thickness of AFRP sheet used, type of wraps applied, type of anchors and diameter of anchor head used. Two types of anchorage system were proposed in the study, i.e. insert anchor system and C-embedded anchor system. The results from this study showed that the proposed anchorage system can improve the contribution of the FRP sheets in carrying the shear force in beams. In addition, the C-embedded anchor system exhibits better performance than the insert anchor system. Lastly, the behaviour of beams strengthened using FRP stirrups with anchored ends can be closely predicted by the ACI 440 design equations applicable for full-wrap scheme.